2001
DOI: 10.1046/j.0007-1323.2001.01860.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laparoscopy on immune function

Abstract: Despite a few contradictory reports, systemic immunity appears to be better preserved after laparoscopic surgery than after open surgery. However, the local intraperitoneal immune system behaves in a particular way when exposed to carbon dioxide pneumoperitoneum; suppression of intraperitoneal cell-mediated immunity has been demonstrated in a number of studies. This feature may be clinically important and should be acknowledged when considering laparoscopic surgery in patients with malignancy or sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
93
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(98 citation statements)
references
References 98 publications
(91 reference statements)
0
93
0
5
Order By: Relevance
“…Laparoscopic surgery has been shown to provide important advantages on the short term when compared to open surgery for the treatment of several malignant diseases with at least the same long term survival (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic surgery has been shown to provide important advantages on the short term when compared to open surgery for the treatment of several malignant diseases with at least the same long term survival (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, IL-6 levels don't increase greatly in the picture of acute appendicitis as result of infection in the gastrointestinal system but do increase in cases where tissue damage occurs due to surgical intervention. [3][4][5] In a study that supports this conclusion, Yildirim et al [1] investigated leukocyte count, IL-6, and C-reactive protein (CRP) levels in patients with prediagnosis of acute appendicitis. They stated that leukocyte count and CRP levels may be helpful in diagnosis of acute appendicitis.…”
Section: Discussionmentioning
confidence: 74%
“…Particularly in patients with cancer, better preserved postoperative immunity may result in more favorable long-term oncological results. It was previously reported that the systemic immune response was better preserved after laparoscopic surgery as compared to after conventional surgery (21)(22). The acute-phase response is a favorable indicator of tissue injury in patients (23).…”
Section: Discussionmentioning
confidence: 99%